Hydrological Conditions Influence Soil and Methane-Cycling Microbial Populations in Seasonally Saturated Wetlands - Maietta, Christine E.; Hondula, Kelly L.; Jones, C. Nathan; Palmer, Margaret A. (Frontiers in Environmental Science, 2020)
Seasonally saturated wetlands are hydrologically dynamic ecosystems that provide a variety of ecosystem services; however, their variable hydrologic conditions may promote greenhouse gas emissions. The extent to which wetlands produce and emit greenhouse gases is intimately tied to the underlying microbial community. We established a linear transect spanning a hydrologic gradient on the margins adjacent to five seasonally saturated wetlands to characterize how water level, saturation duration, and frequency of wet-dry cycles influenced the soil and methane-cycling microbial community composition. We found that the soil and methane-cycling microbial community diversity and structure were strongly related to changes in water level and saturation duration but not saturation frequency. Soils that experienced inundation or saturation for more than 50% of the year harbored a soil microbial composition distinct from soils that were rarely saturated or inundated. While soils closer to the wetland basin supported a higher relative abundance of methanogens, methane-oxidizing microbes were present across the entire topographic gradient; however, the composition shifted from a primarily anaerobic to aerobic methanotroph community. Findings suggest that soil and methane cycling microorganisms are influenced by the hydrologic conditions of the soil, with methane producers being restricted to specific ranges and methane oxidizers able to occur under a variety of hydrologic conditions. The mechanisms driving methane oxidation by the latter, however, may depend on the hydrologic conditions.